Liprin-α1 Expression in Tumor-Infiltrating Lymphocytes Associates with Improved Survival in Patients with HPV-Positive Oropharyngeal Squamous Cell Carcinoma - Sjöblom Anni; Pehkonen Henna; Jouhi Lauri; Monni Outi.; Randén-Brady Reija; Karhemo Piia-Riitta; Tarkkanen Jussi; Haglund Caj.; Mattila Petri.; Mäkitie Antti.; Hagström Jaana; Carpén Timo (Springer, 2025)
Background: Liprin-α1 is a scaffold protein involved in cell adhesion, motility, and invasion in malignancies. Liprin-α1 inhibits the expression of metastatic suppressor CD82 in cancers such as oral carcinoma, and the expression of these proteins has been known to correlate negatively. The role of these proteins has not been previously studied in human papillomavirus (HPV)-related head and neck cancers. Our aim was to assess the clinical and prognostic role of liprin-α1 and CD82 in HPV-positive oropharyngeal squamous cell carcinoma (OPSCC) in comparison to HPV-negative OPSCC.
Methods: The data included 139 OPSCC patients treated at the Helsinki University Hospital (HUS) during 2012-2016. Immunohistochemistry was utilized in HPV determination and in biomarker assays. Overall survival (OS) was used in the survival analysis.
Results: Stronger expression of liprin-α1 in tumor-infiltrating lymphocytes (TILs) was linked to lower cancer stage (p < 0.001) and HPV positivity (p < 0.001). Additionally, we found an association between elevated expression of liprin-α1 and weak expression of CD82 in tumor cells (p = 0.029). In survival analysis, we found significant correlation between favorable OS and stronger expression of liprin-α1 in TILs among the whole patient cohort (p < 0.001) and among HPV-positive patients (p = 0.042).
Conclusions: Increased liprin-α1 expression in the TILs is associated with favorable prognosis in OPSCC, especially among HPV-positive patients.